Legal Reconstruction of Electronic Land Rights Certificates Burdened with Mortgage Rights as a Form of Credit Guarantee Banking - Richa Rahmatin; Fathul Laila; Nur Chanifah (Rescollacom (Research Collaborations Community), 2025)
Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia Number 1 of 2021 concerning electronic certificates is a new regulation that changes the rules regarding land title certificates which were originally in book form to electronic form. Several of these regulations regulate changes in procedures and mechanisms but do not regulate in depth if the electronic land title certificate is pledged at the bank by someone else who is not the certificate owner and during the credit application process contains elements of fraud in it. The ambiguity of this regulation has caused several disparities in the judge's decisions which have significant legal impacts on justice seekers. This study examines two things, the first discussing the legal regulation of electronic land title certificates burdened with mortgage rights as a form of credit guarantee at the bank and the second discussing the legal reconstruction of electronic land title certificates burdened with mortgage rights as a form of credit guarantee at the bank in future regulations. This research method uses normative legal research methods with a statutory approach, a conceptual approach and a case approach. This study uses primary, secondary and tertiary legal materials by conducting a literature study and analyzing using legal interpretation. The results of this study are first, the regulation on land title certificates does not clearly regulate certificates that are pledged at the bank so that they are burdened with mortgage rights where the customer who applies is not the owner of the certificate. Second, to solve the first problem, it must be regulated with certainty regarding electronic land title certificates if they are pledged by someone else at the bank or if there is an element of fraud in the credit application.